2021
DOI: 10.3389/fgene.2021.671079
|View full text |Cite
|
Sign up to set email alerts
|

Tracing the Distribution of European Lactase Persistence Genotypes Along the Americas

Abstract: In adulthood, the ability to digest lactose, the main sugar present in milk of mammals, is a phenotype (lactase persistence) observed in historically herder populations, mainly Northern Europeans, Eastern Africans, and Middle Eastern nomads. As the –13910∗T allele in the MCM6 gene is the most well-characterized allele responsible for the lactase persistence phenotype, the –13910C > T (rs4988235) polymorphism is commonly evaluated in lactase persistence studies. Lactase non-persistent adults may develop … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
2
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 87 publications
(130 reference statements)
0
6
0
Order By: Relevance
“…The Arab variant G‐13915 and the rare allele T‐14011, both found in Tacuarembó with an allelic frequency of 0.4%, were previously reported at very low frequencies in Brazilians (Friedrich, Santos, et al, 2012; Guimarães Alves et al, 2021), while the first one was also reported in Ecuadorians (Paz y Miño et al, 2016). Variant G‐13915 exhibits it highest frequency in Saudi Arabia (57%), with minor frequencies in other Middle East Arabs, North Africa, and East Africa (Table A1).…”
Section: Discussionmentioning
confidence: 84%
See 4 more Smart Citations
“…The Arab variant G‐13915 and the rare allele T‐14011, both found in Tacuarembó with an allelic frequency of 0.4%, were previously reported at very low frequencies in Brazilians (Friedrich, Santos, et al, 2012; Guimarães Alves et al, 2021), while the first one was also reported in Ecuadorians (Paz y Miño et al, 2016). Variant G‐13915 exhibits it highest frequency in Saudi Arabia (57%), with minor frequencies in other Middle East Arabs, North Africa, and East Africa (Table A1).…”
Section: Discussionmentioning
confidence: 84%
“…Particularly, we have estimated in the population of Tacuarembó a mean of 80.4% of European contribution based on nDNA, and previously Bonilla et al (2015) had estimated a mean of 77.1% for the whole country. Recently, Guimarães Alves et al (2021) estimated 83.4% of European ancestry proportion for a sample of Uruguay, and reported a frequency of the LP associated allele (T‐13910) of 35.3% in Uruguay, the highest among the American populations they have analyzed. Similar frequencies of T‐13910 were reported in Euro‐Brazilians from southern Brazil, while in other South American cosmopolitan populations, with smaller European contributions, T‐13910 allele frequency ranged from 10% to 22%.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations